1. KNOWLEDGE, ATTITUDES, PRACTICES FOR MALARIA PREVENTION OF FARMERS AND ASSOCIATED FACTORS IN IA TOI COMMUNE, IA H'DRAI DISTRICT, KONTUM PROVINCE IN 2022 (Vietnam Journal of Community Medicine, 2022)
Objective: To describe knowledge, attitudes and practices of malaria prevention of cultivators andanalyze some factors affecting malaria prevention practice of farmers in Ia Toi commune, Ia H’Draidistrict, Kon Tum province in 2022Research method and time: The implementation period of the study was from January 2022 tothe end of August 2022, with the participation of 230 people. Applying analytical cross-sectionalresearch method. Using descriptive statistics to show the frequency, percentage of qualitativevariables whilst statistical analysis was used with χ2, OR (95% CI) to test some factors associated tothe study participants’ practices on malaria prevention with the significance level p
Keywords: Malaria, farmers, associated factors, Ia Toi, Kon Tum.